Rise of Fundamentalist Discourse and the Reassertion of Modern Ethos. (1st January 2015) - ,
Abstract : The religious resurgence in the contemporary world has generally been described as a threat to global peace in general and to the axiological centrality of humanist values i.e. autonomy and self-determination, in particular. This threat presumes an oversimplified version of fundamentalism which is not only predominantly modernistic but also views religious reservations against modern life-world in abstraction to postmodern critique on the colonization of modern discursive practices. Islamic discourse determines the limit of modernity in the non-Western, post-colonial world; on the other hand, it provides substantive theoretical resistance to anti-foundationalist, contingent and relativistic postmodernism prevailing in Eurocentric cultures. In this way, Islamic discourse naturally performs two functions simultaneously which has the potential to be instrumentalised for the sustenance of modern institutional order.